Natural and Cultural Heritage and its Tourism Importance in Maysan City, South Eastern Iraq - Al-Zubaidi, Aqeel A.; Q. Hadi, Safaqis; Al-Marsoumi, Jasib S.; Al Kinani, Khadir A. (Al-Adab Journal, 2019)
The data was collected through field surveys of natural, archaeological, and religious and heritage sites; as well as visiting of some government institutions to access reports and text available in their libraries. The study explains the importance of natural heritage, such as the presence of Hor Al- Huwaiza, one of the four components listed on the World Heritage List, because of the diverse natural ecosystems and richness of biodiversity, especially the existence of threatened species of exceptional global value. The presence of more than 440 sites of cultural or archaeological heritage, spread over all the districts and areas of Maysan province, which includes different periods of civilizations: The Stone ages, Sumerian, Akkadian, Babylonian, Achmainic, Firthic, Sasanian, and Islamic civilizations. Islamic Religious sites such as: Ali al-Gharbi, Ali al-Sharqi and Obaidullah ibn Ali. Christian sites such as Umm Al-Ahzan Church, Mar Youssef Church. Jewish sites such as Al- Uzair Prophet; Sabean in addition to many heritage sites. Tourism is one of the productive economic sectors that contribute to increasing local and national income. Therefore, sustainable tourism and ecotourism must be supported and promoted to create jobs and improve the living standards of the local population, by providing infrastructure and preparing plans and programs that develop ecotourism in Huwaiza and adjacent natural areas, religious and archaeological tourism, and other kinds of tourism in an attempt to sustain the elements of natural, cultural and religious heritage and provide employment opportunities for the local population.